2022
DOI: 10.1097/md.0000000000028767
|View full text |Cite
|
Sign up to set email alerts
|

What makes acute cholecystitis recur after removing the percutaneous cholecystostomy tube?

Abstract: Percutaneous transhepatic gallbladder drainage (PTGBD) is an alternative treatment option for acute cholecystitis. However, the disease may recur after PTGBD catheter removal. This study aimed to evaluate the role of endoscopic sphincterotomy and other risk factors in reducing the recurrence of cholecystitis.We retrospectively analyzed data from 1088 patients who underwent PTGBD for cholecystitis at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Of the 36 patients who had PTGBD removed after the improvement of cholecystitis, the incidence rate of biliary tract complications, including the recurrence of cholecystitis was as high as 22.2%. Another retrospective study by Jun et al 26 T A B L E 1 Patient characteristics in the two treatment groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 36 patients who had PTGBD removed after the improvement of cholecystitis, the incidence rate of biliary tract complications, including the recurrence of cholecystitis was as high as 22.2%. Another retrospective study by Jun et al 26 T A B L E 1 Patient characteristics in the two treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 36 patients who had PTGBD removed after the improvement of cholecystitis, the incidence rate of biliary tract complications, including the recurrence of cholecystitis was as high as 22.2%. Another retrospective study by Jun et al 26 investigated 115 patients who underwent PTGBD for acute cholecystitis. After improvement of cholecystitis, patients were discharged with an indwelling PTGBD catheter and were followed up every 4–12 weeks until the removal of the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the catheter can frequently dislocate from the gallbladder and necessitate reinsertion. 16 Patients with a non-independent lifestyle could be more vulnerable to sepsis secondary to recurrent cholecystitis. Hersey et al 2 reported on the safety and efficacy of CDS placement with 33 patients in 2015.…”
Section: Discussionmentioning
confidence: 99%